Molecular Detection of Babesia motasi in a Goat – First Report from Kerala - Prathyusha, S; R, Radhika; Lakshmanan, Bindu; K, Devada; A, Javed Jameel (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Caprine babesiosis is a tick borne haemoprotozoan infection less frequently reported from Kerala. In the present report, we document a confirmed case of Babesia motasi for the first time in the state. A Sirohi Kathiavari crossbred goat was presented to the University Veterinary Hospital (UVH), Kokkalai with symptoms of anorexia and pyrexia. On blood smear examination, large and small forms of Babesia organisms in Giemsa’s stain could be detected. Complete blood count revealed hypochromic microcytic anaemia with thrombocytopenia. Molecular confirmation was done with polymerase chain reaction (PCR) targeting 18S rRNA gene. A 390 bp fragment was obtained and sequenced which was confirmed as Babesia motasi. Babesia ovis or Theileria spp., could not be detected by PCR. This study reports the molecular confirmation of two forms of B. motasi in a crossbred goat from Kerala.